Diversity in randomized clinical trials for peripheral artery disease: a systematic review - Chandler Long; Abimbola O. Williams; Alysha M. McGovern; Caroline M. Jacobsen; Liesl M. Hargens; Sue Duval; Michael R. Jaff (BMC, 2024)
Abstract Background Significant race and sex disparities exist in the prevalence, diagnosis, and outcomes of peripheral artery disease (PAD). However, clinical trials evaluating treatments for PAD often lack representative patient populations. This systematic review aims to summarize the demographic representation and enrollment strategies in clinical trials of lower-extremity endovascular interventions for PAD. Methods Following the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we searched multiple sources (Medline, EMBASE, Cochrane, Clinicaltrials.gov, WHO clinical trial registry) for randomized controlled trials (RCTs), RCT protocols, and peer-reviewed journal publications of RCTs conducted between January 2012 and December 2022. Descriptive analysis was used to summarize trial characteristics, publication or study protocol characteristics, and the reporting of demographic characteristics. Meta-regression was used to explore associations between demographic characteristics and certain trial characteristics. Results A total of 2,374 records were identified. Of these, 59 met the inclusion criteria, consisting of 35 trials, 14 publications, and 10 protocols. Information regarding demographic representation was frequently missing. While all 14 trial publications reported age and sex, only 4 reported race/ethnicity, and none reported socioeconomic or marital status. Additionally, only 4 publications reported clinical outcomes by demographic characteristics. Meta-regression analysis revealed that 6% more women were enrolled in non-European trials (36%) than in European trials (30%). Conclusions The findings of this review highlight potential issues that may compromise the reliability and external validity of study findings in lower-extremity PAD RCTs when applied to the real-world population. Addressing these issues is crucial to enhance the generalizability and impact of clinical trial results in the field of PAD, ultimately leading to improved clinical outcomes for patients in underrepresented populations. Registration The systematic review methodology was published in the International Prospective Register of Systematic Reviews (PROSPERO: CRD42022378304).